2005
DOI: 10.1250/ast.26.403
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear vibrations and chaos in gongs and cymbals

Abstract: This paper summarizes some results obtained in the last few years for the modeling of nonlinear vibrating instruments such as gongs and cymbals. Linear, weakly nonlinear and chaotic regimes are successively examined. A theoretical mechanical model is presented, based on the nonlinear von Kármán equations for thin shallow spherical shells. Modal projection and Nonlinear Normal Mode (NNM) formulation leads to a subset of coupled nonlinear oscillators. Current developments are aimed at using this subset for sound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 14 publications
2
48
0
Order By: Relevance
“…2 and its dimensional counterpartF readsF = Eh 4 εa 4 F. For a typical circular plate having the dimension of a cymbal, i.e. with E=110 GPa, h=1 mm, a= 0.2 m and ε = 12(1 − ν 2 ) with ν = 0.33, the critical non-dimensional force F cr = 15.92 leads to a dimensional forcingF=102.35 N, which is significantly larger than the experimental values needed to obtain chaotic behaviour, which are of the order of 2 to 10 N [8,50]. In section 4, it will be shown that considering an imperfection (unavoidable in real plates) significantly reduces this critical value to those observed experimentally.…”
Section: Generic Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…2 and its dimensional counterpartF readsF = Eh 4 εa 4 F. For a typical circular plate having the dimension of a cymbal, i.e. with E=110 GPa, h=1 mm, a= 0.2 m and ε = 12(1 − ν 2 ) with ν = 0.33, the critical non-dimensional force F cr = 15.92 leads to a dimensional forcingF=102.35 N, which is significantly larger than the experimental values needed to obtain chaotic behaviour, which are of the order of 2 to 10 N [8,50]. In section 4, it will be shown that considering an imperfection (unavoidable in real plates) significantly reduces this critical value to those observed experimentally.…”
Section: Generic Resultsmentioning
confidence: 89%
“…A convenient and reproducible way to experimentally study the chaotic vibrations of gongs and cymbals consists in harmonically forcing the structure with an increasing amplitude. Numerous experiments on differents cymbals and gongs have been performed and are reported in [9,7,10,8,11,12]. The generic observation, that is also valid for plates and shells, reveals a scenario for the transition to chaotic vibrations including two bifurcations, separating three distinctive regime.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations